'Savage Beauties'. Alexander McQueen's performance of posthuman bodies. Issue 2 (3rd July 2017) - Stępień, Justyna
ABSTRACT: This paper focuses on the question of how fashion can reconfigure a human body out of its once common generic and symbolic modes of representation. Immersed in the bioscientific and biotechnological environment, a body has become an increasingly complex and contradictory entity that cannot be considered from a traditional perspective or conceptualization. Alexander McQueen's projects and shows addressed these concerns against the background of the mainstream fashion industry's socio-cultural normalization, opening up the body to new channels of interactivity with the nonhuman. Drawing on Deleuze and Guattari's theoretical framework and its new materialist reworking, this article discusses the human and nonhuman relationality in the designer's works to show how multiple modes of intervention of different matters trigger constant metamorphosis of body processes. Ultimately, the article reveals how, thanks to their material extensions, McQueen's posthuman bodies are assemblages that unfold new forms of subjectivities.